Analisis Penyelesaian Skripsi berdasarkan Gender di IAIN Langsa - Anggria Novita; Siti Atri Handayani (Jurnal Anifa: Studi Gender dan Anak, 2020)
Completion of thesis is a final project that must be done by students as a condition to get a bachelor's degree. This study aims to examine the completion of the thesis based on gender to students majoring in mathematics education in FTIK IAIN Langsa and the obstacles experienced by students. This research is a qualitative research, using descriptive research methods. Data collection techniques namely by interviewing Mathematics Education Students of FTIK IAIN Langsa class of 2015.This study revealed that the completion of the thesis was based on gender (male and female students) are different, the difference can be seen from the level of student speed in completing the thesis. The study shows that female students are more instrinsically motivated than male students, so that the increase in thesis completion charts in a timely manner is more dominated by female students.